General Average and Jettison: The Policy Under Marine Insurance to Assist Master to Make Decision During Distress - Zuhairah Ariff, Abd Ghadas; Mohd Sharifuddin, Ahmad (2017)
The master or captain is a person who has ultimate command of the vessel who bears great responsibilities towards the ship owner and cargo owner for safe voyage. The master is objectively accountable for every decision. However, the master usually encountered with situation where the loss cannot be avoided without scarifies some cargos on board or incur extra ordinary expanse (General Average and Jettison). The objectives of research are to analyze the potential and the limitation of General Average and Jettison to assist the master in making good decision during distress. In addition, the research will identify the advantage and disadvantage of choosing either one of them toward the interest of ship owner and cargo owner. It is a doctrinal research which descriptive in nature. The paper discuss and examine the situation by referring to the main sources of law as an authority under the law of marine insurance and other related laws. It is clear that there are differences between General Average and Jettison in which the former requires strict compliance with General Average elements such as common marine adventure and in time of peril otherwise it will consider as the latter. Moreover, General average and jettison is a relief for master since any act of avoiding loss to the voyage including throwing cargo off board is covered by the insurance. However, the main concern is the uniqueness of General Average where the scarified cargo entitle for the damages even though having no insurance coverage since the payment is claimed from those who survived. Meanwhile, the jettison is a risk covered under the policy of marine insurance. Therefore, it is crucial for master to have the knowledge on the status of cargo and ship before deciding to choose General Average or Jettison.